Politically Motivated Bar Discipline - James E. Moliterno (Washington University Law Quarterly, 2005)
Bar discipline and admission denial have a century-long history of misuse in times of national crisis and upheaval. The terror war is such a time, and the threat of bar discipline has once again become an overreaction to justifiable fear and turmoil. Political misuse of bar machinery is characterized by its setting in the midst of turmoil, by its target, and by its lack of merit. The current instance of politically motivated bar discipline bears the marks of its historical antecedents.
Keywords: Lawyers -- Discipline; Government attorneys; War on Terrorism; 2001-2009; Dissenters; United States